Goodluck Jonathan, The Champion of Women in the Contemporary Nigeria, 2010-2015: An Appraisal - Ibekwe, Juliet Chinenye; Chidiobi, Okechukwu Christian (Advances in Social Sciences Research Journal, 2022)
The meteoric ascendency of Dr. Goodluck Ebele Jonathan to the office of the number one citizen of Nigeria is not just seen by many as providential but could be also termed as a journey of grace. The Goodluck Jonathan’s led administration spanned from 2010 to 2015. He was elected as the 7th democratic president of Nigeria in 2011 general/ Presidential election for a four year tenure which ended in 2015 and in which he failed the bid to be reelected. The administration of President Goodluck Jonathan was characterized or bedeviled by severe criticism, a development which contributed largely to his exit in 2015 after just a tenure in office. These criticisms were apparently predicated on a number of pertinent national issues which were economic, socio-political and even religious in nature. The worst being the inability of the government to combat the upsurge in Boko Haram menace, their failure to rescue the alleged abducted Chibok Girls as well as massive cases of corruption among top public office holders and the presumed laissez-faire attitude of the president in addressing the ugly development. In spite of these avalanche of criticisms however, one major area of interest in which the Jonathan’s administration was greatly commended even by the international community was on women empowerment. The administration was adjudged to have performed well above international average of 20%, and it is in view of this that the idea behind this paper is conceived, to appraise the effort of the president in enhancing the status of the Nigerian women. Jonathan appointed many women into positions of authorities and provided avenues by which a good number of them were elected into political offices. There was also empowerment programs such as skill acquisitions and micro-credit loan schemes meant to alleviate the sufferings of the ordinary women and put smiles on their faces. Although this administration could not realize the 5% affirmative action plan recommended as benchmark in Beijing, China in 1985, it is however good to know that about 33% of this well above international average was said to have been achieved. These and a few related issues were discoursed in this paper. Feminist theory was adopted as a theoretical framework to explain the gender based discrimination against women and therefore focuses on promotion of women’s rights and interests. In view of this, measures that could help to end this unhealthy practices and that can free women from the shackles of age-long domination of men were thus suggested.